THE EXPRESSION OF MANAGERIAL LEADERSHIP IN SOCIAL SERVICE ORGANIZATIONS - Čižikienė, Janina; Urmanavicius, Justas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of social service organizations that provide modern social services is to give quality social services that would help a person (family) to become independent and able to integrate into society. Successful operation of organizations is ensured by the ability of managers to lead, motivate employees to achieve the set goals, and promote cooperation with stakeholders. Therefore, managerial leadership is especially important to influence the activities of the members of the organization, creating conditions for continuous improvement and cooperation.  A leader must be able to bring employees into a team, evaluating achievements and facilitating social interaction between team members, and strive to continually improve employees’ ability to provide individual, customer-oriented services. The aim of the article is, based on theoretical analysis and empirical research, to highlight the peculiarities of managerial leadership in social service organizations and to define the influence of leadership in the process of providing social services to employees, service recipients, and stakeholders. The research revealed what the most important characteristics, personal qualities, and competencies of a leader in an organization are and what influence managerial leadership has when organizing and providing quality social services. The research identified the aspects of managerial leadership that would help ensure successful operation of organizations when providing effective support to those experiencing exclusion in the community.